Gerrard Winstanley and the Digger Movement. A bibliographical survey, [by] H. Tamura
Repr.: Keizaigaku Ronsan. (The Journal of Economics, Chuo University). Vol. VII, 1966, no. 5, p. 57-100. Japanese text.